Whether the start time of elective lung surgery impacts perioperative outcomes and cost? - A-Lai, Gu-Ha; Hu, Jian-Rong; Xu, Zhi-Jie; Yao, Peng; Zhong, Xia; Wang, Yu-Cheng; Lin, Yi-Dan (Frontiers in Surgery, 2022)
Background Fatigue and long work hours of surgeons attracts increasing concerns in recent years. We aimed to explore whether starting time was associated with perioperative outcomes and cost for elective lung surgery. Methods A retrospective study was conducted on elective lung surgery patients at a high surgery-volume center between September 2019-November 2019. Patients were divided into “early start group” if surgery start time was before 4pm while “late start group” was defined as surgery started after 4pm. Perioperative outcomes and total hospital costs were compared between two groups. Besides, multivariable logistic regression analysis was performed to identify whether start time was a risk factor for postoperative hospital duration, total hospital cost and length of operation time. Results A total of 398 patients were finally enrolled for analysis in this study. Of all the cases, 295 patients were divided into early start group while 103 patients belonged to late start group. Baseline characteristics were all comparable between the two groups. Concerning outcomes, there were no differences in postoperative hospital duration, operation time, complication incidence and other outcomes while the total hospital cost tended to be different but still no statistical difference (P=0.07). In multivariable logistic regression analysis, surgery start late was still found not to be a risk factor for long postoperative hospital duration, high hospital cost and long surgery time. Conclusion In elective lung surgery, perioperative outcomes and cost were similar between early and late start group, it was not necessary to worry about surgery order for these patients.